Gadolinium leakage in ocular structures is common in lacunar infarction - Förster, Alex; Al-Zghloul, Mansour; Wenz, Holger; Böhme, Johannes; Groden, Christoph; Alonso, Angelika (Stroke, 2019)
Background and Purpose - We investigated the frequency and pattern of blood-brain barrier, as well as blood-retina barrier, impairment in acute lacunar infarction as demonstrated by hyperintense acute reperfusion marker and gadolinium leakage in ocular structures (GLOS), respectively, on fluid-attenuated inversion recovery images.Methods - Acute lacunar infarction patients who underwent repeated magnetic resonance imaging after intravenous contrast agent administration were identified and the presence of GLOS in the anterior chamber and vitreous body and hyperintense acute reperfusion marker noted on fluid-attenuated inversion recovery.Results - Overall, 24 acute lacunar infarction patients (median age 64.5 years; interquartile range, 54-78 years) were included. On contrast-enhanced fluid-attenuated inversion recovery, GLOS was observed in 11 (45.8%) patients: in 4 (16.7%) in the anterior chamber only and in 7 (29.2%) in the anterior chamber and vitreous body. In all patients, GLOS was bilateral and symmetrical. In patients with GLOS in the anterior chamber only, the time between initial and follow-up magnetic resonance imaging was significantly shorter (7.5 [interquartile range, 4.25-11.5] hours) compared with patients with GLOS in the anterior chamber and vitreous body (28 [interquartile range, 10-43] hours; P=0.047). Hyperintense acute reperfusion marker could not be demonstrated in any of the patients.Conclusions - In acute lacunar infarction patients, unlike hyperintense acute reperfusion marker, GLOS is a frequent finding and shows a similar temporal evolution like in larger ischemic stroke.
Originally published November 21, 2018
Gesehen am 23.10.2019